1999
DOI: 10.1007/s002130050856
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ketamine on gating of auditory evoked potentials and prepulse inhibition in rats

Abstract: Schizophrenic patients suffer from deficits in information processing. Patients show both a decrease in P50 gating [assessed in the conditioning-testing (C-T) paradigm] and prepulse inhibition (PPI), two paradigms that assess gating. These two paradigms might have a related underlying neural substrate. Gating, as measured in both the C-T paradigm (the gating of a component of the auditory evoked potential (AEP)], and PPI can easily be measured in animals as well as in humans. This offers the opportunity to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 54 publications
(59 reference statements)
11
50
1
Order By: Relevance
“…41 With regard to PPI, specifically, the findings in healthy patients are mixed, with one study reporting disruption of 'PPI-like' auditory gating following treatment with ketamine, 42 some studies reporting no effects of ketamine on PPI, 43,44 and others reporting enhancement of PPI. [45][46][47] However, it is clear that patients with schizophrenia do have altered PPI 1,5,[48][49][50] and that in nonhuman primates 51,52 and rodents, [53][54][55][56] treatment with NMDA antagonists disrupts PPI. Why there are discrepancies in the effects of NMDA antagonists on PPI between clinical and preclinical studies remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…41 With regard to PPI, specifically, the findings in healthy patients are mixed, with one study reporting disruption of 'PPI-like' auditory gating following treatment with ketamine, 42 some studies reporting no effects of ketamine on PPI, 43,44 and others reporting enhancement of PPI. [45][46][47] However, it is clear that patients with schizophrenia do have altered PPI 1,5,[48][49][50] and that in nonhuman primates 51,52 and rodents, [53][54][55][56] treatment with NMDA antagonists disrupts PPI. Why there are discrepancies in the effects of NMDA antagonists on PPI between clinical and preclinical studies remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of N50 suppression, the rodent analogue of P50 in humans, also denoted as N40, have also implicated monoaminergic neurotransmitter systems in the modulation of P50 suppression. As in humans, acute D-amphetamine reduced gating of the N40 component in rodents (Adler et al, 1986;de Bruin et al, 1999). Thus, Adler et al (1986) conclude that 'catecholamines have significant modulatory effects on the gating, amplitude, and latency of P50 in humans and rats.'…”
Section: P50 Suppressionmentioning
confidence: 90%
“…Some relationship of P50 suppression to PPI was noted during the early part of the test session, when the process of habituation of the startle reflex is active (Oranje et al, 1999). Similarly, PPI and AEP gating in rats are not correlated and the two phenomena exhibit differential sensitivities to drug treatments (de Bruin et al, 1999). These results derived from both humans and rodents suggest that different neural mechanisms underlie PPI and P50 suppression.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most, but not all, studies in rats showed impairments of N40 -gating (the putative rat correlate of the human N100) with NMDAR blocking (Miller et al, 1992;de Bruin et al, 1999;Swerdlow et al, 2006). However, no effect of NMDAR antagonists on auditory gating was observed in a study in mice (Connolly et al, 2004).…”
Section: Auditory Gatingmentioning
confidence: 99%